Circulating tumor cells and coagulation—Minireview. (June 2017) - Bystricky, Branislav; Reuben, James M.; Mego, Michal
Highlights: Venous thromboembolic events are frequent complication in patients with cancer. Circulating tumor cells (CTC) are associated with prothrombotic state. CTC could activate coagulation via interaction with tissue factor, coagulation factors, platelets and endothelial cells. Abstract: Venous thromboembolic events in cancer patients signify poor prognosis. Prophylactic treatment of ambulatory patients with anticoagulants is currently not recommended. Circulating tumor cells, either directly or indirectly, are associated with prothrombotic state. In this review, we discuss various interactions of circulating tumor cells with the coagulation pathway in cancer patient.